Philosophy and Its Relation to Religion and Arts - Vladimirovich Kondratiev, Konstantin (2017)
Presently existing philosophical schools and tendencies show a fundamentally different form of the very philosophical thinking, and therefore, radically different solutions to the problem of the essence of philosophy. One way to find an answer to the question of what philosophy represents is to compare philosophy with other forms of spiritual culture that are related to it: art, religion, and science. The article covers the variants of the mutual correlation of the concepts “philosophy”, “religion”, “art” and attempts to compare them. On the one hand, these phenomena cannot be clearly opposed to each other because of their obvious connection, on the other hand, their identification will also pose a serious threat to a correct understanding of the system of spiritual culture of modern society